Effect of whole body vibration on clinical and metabolic outcomes in adults with type 2 diabetes: an observational pilot trial. (2nd June 2021) - Michels, Manuella de L; Spivakoski, Camila S; Réus, Bruna da S; Alves, Débora M dos S; Mattje, Priscila ND; Hohl, Alexandre; Ronsoni, Marcelo F; van de Sande‐Lee, Simone
Abstract: The objective of this trial was to evaluate the effect of 28Hz whole body vibration on glycaemic control and other metabolic parameters in adults with type 2 diabetes (T2D). Twenty‐four adults with T2D on oral antidiabetic agents, with a baseline glycated haemoglobin (HbA1c ) 6.5–9.0% (48–75mmol/mol), were randomised into two groups. The control group (CG) was advised to adopt lifestyle modifications, and the intervention group (IG) received the same orientations plus a vibrating platform for daily use for 12 weeks. Data from 22 patients were analysed (one from each group was excluded). Baseline characteristics of both groups were similar except for triglycerides, which were higher in the CG (111.8±39.9 vs 188.9±68.8mg/dL [1.26±0.45 vs 2.13±0.78mmol/L], p<0.05). After 12 weeks, there was a significant reduction in HbA1c in the IG (7.69±0.49 vs 7.17±0.77% [60.5±5.39 vs 54.9±8.74mmol/mol], p<0.05), not observed in the CG (8.05±0.98 vs 7.92±1.07% [64.5±10.78 vs 63.1±11.77mmol/mol], p=0.52). A non‐significant trend for weight loss in IG was observed (78.14±10.47 vs 77.14±11.08kg, p=0.06). There were no significant differences between the groups regarding fasting blood glucose or any other clinical and biochemical variables analysed. Daily use of the vibrating platform for 12 weeks resulted in improved HbA1c in adults with T2D. Further studies are needed to better define the role of whole body vibration as an adjuvant in T2D treatment. Copyright © 2021 John Wiley & Sons.